Hashimoto’s Encephalopathy Mimicking Viral Encephalitis: A Case Report - Yu, Miaomiao; Yang, Yu; Ma, Xianyi; Xie, Yinyin; Sun, Ningning; Meng, Hongmei (Frontiers in Neuroscience, 2020)
Hashimoto’s encephalopathy (HE) is a rare neuropsychiatric syndrome characterized by elevated levels of anti-thyroid antibodies. Diverse manifestations make timely diagnosis of HE difficult. Herein, we report a case of HE, in which the clinical symptoms and laboratory test results mimicked viral encephalitis. A 59-year-old male patient, who presented with a fever, headache, slow and unclear speech, sentence confusion, elevated levels of anti-thyroid antibodies in the serum, an increased white blood cell count, and positivity for anti-thyroid antibodies in the CSF, was finally diagnosed with HE and responded well to a small dose of methylprednisolone. This report helps bring the attention of clinicians to the fact that HE should be considered when cases of unexplained encephalopathy are encountered.